A novel algorithm for space camera geometry parameters on-orbit calibration. (June 2021) - Wang, Weizhi; Wang, Qiaoxia; Zong, Yunhua; Di, Jingjing; Ren, Yuning; Gao, Weijun
Highlights: We propose method for space camera on-orbit geometry parameters calibration. We simplify the expression of the accuracy estimation for calibration parameters. Centroiding errors affects the accuracy of the internal and external parameters. Periodical law of the calibration parameters revealed by thermal vacuum test. Abstract: The precision of geometry parameters is important for stereo mapping tasks. The current methods mainly by ground calibration field which exhibit disadvantages. Inspired by simplified method with laser reference beam we proposed in previous work, a novel on-orbit calibration method based on dual vector attitude determination algorithm is proposed, overcoming the limitation of previous methods. First, a single camera calibration model is established with the proposed method. Errors introduced by input parameters are then analyzed and expressed by simplified expressions. Furthermore, residual errors between the two algorithms are calculated. Finally, an experimental system with two-array cameras is set up in a vacuum chamber with well vibration isolation. The results show that the proposed method is well performance in real time with high accuracy. Moreover, the phenomenon of the periodic sinusoidal change of the angle between cameras in a circle is revealed, which is essential to stereo mapping tasks.